Pengaruh waktu pemangkasan pucuk dan sisa buah setelah penjarangan terhadap hasil produksi tanaman semangka (Citrullus vulgaris schard) - Anita Dwi Yuriani; Eny Fuskhah; Yafizham yafizham (Journal of Agro Complex, 2019)
ABSTRACT  The objective of this research was to know growth and the production of watermelon plants through the treatment of pruning time on shoots and the amount of residual fruit after thinning. The research was carried out on Klaten Watermelon Clay, located in Genukan Village, Wedi Sub-district, Klaten District, and at the Laboratory Chemistry and Food Nutrition Faculty of Animal and Agricultural Sciences, Diponegoro University from February to May 2017. The research was arranged using completely randomized factorial design with the first factor being shoot pruning time (P1 = no trimming, P2 = 3rd week, P3 = 6th week, P4 = 3rd and 6th week) and the second factor was the rest of the fruit after thinning (Q1 = without thinning, Q2 = thinning leaves 1 piece, Q3 = thinning leaves 2 pieces). The results showed the treatment of pruning of shoots and the remaining fruit after spacing did not affect the growth plant height and number of leaves watermelon until 8th week. However pruning of shoots 3rd week and 6th week can affect fruit diameter, fresh fruit weight, and fruit sugar levels. Treatment of the remaining fruit after the spacing is pruned 2 pieces affect the diameter of fruit and fresh weight of fruit while the rest of the fruit after spacing is purned 1 pieces fruit affect the fruit sugar levels. Keywords: watermelon, pruning, thinning, production ABSTRAK  Penelitian bertujuan untuk mengetahui pertumbuhan dan hasil produksi tanaman buah semangka melalui perlakuan waktupemangkasan pada pucuk dan jumlah sisa buah setelah penjarangan. Penelitian ini dilaksanakan pada di lahan Sahabat Semangka Klaten, yang terletak di Desa Genukan, Kecamatan Wedi, Kabupaten Klaten, dan di Laboratorium Kimia dan Gizi Pangan Fakultas Peternakan dan Pertanian Universitas Diponegorodari bulan Juli - September2017. Penelitian disusun menggunakan rancangan acak lengkap factorial dengan faktor pertama adalah waktu pemangkasan pucuk (P1 = tanpa pemangkasan, P2 = minggu ke 3, P3 = minggu ke 6, P4 = minggu ke 3 dan 6) danfaktor kedua adalah sisa buah setelah penjarangan (Q1 = tanpa penjarangan, Q2 = penjarangan disisakan 1 buah, Q3 = penjarangan disisakan 2 buah). Hasil penelitian menunjukan perlakuan pemangkasan pucuk dan sisa buah setelah penjarangan tidak mempengaruhi pertumbuhan tinggi tanaman dan jumlah daun semangka sampai minggu ke 8. Namun pemangkasan pemangkasan pucuk minggu ke 3 dan 6 mempengaruhi diameter buah, bobot segar buah, dan kadar gula buah. Perlakuan sisa buah setelah penjarangan yang dijarangkan 2 buah mempengaruhi diameter buah dan bobot segar buah sedangkan sisa buah setelah penjarangan yang dijarangkan 1 buah mempengaruhi kadar gula buah.Kata Kunci: semangka, pemangkasan, penjarangan, produksi